Knowledge, Utilization and Associated Factors of Postpartum Family Planning Among Women Who Had Delivered a Baby in the Past Year in Oromia Regional State, Ethiopia - Seifu B; Yilma D; Daba W (Dove Medical Press, 2020)
Benyam Seifu,1 Delelegn Yilma,1 Workinesh Daba2 1College of Medicine and Health Sciences, Ambo University, Ambo, Oromia Regional State, Ethiopia; 2School of Nursing and Midwifery, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Benyam SeifuCollege of Medicine and Health Sciences, Ambo University, P.O. Box: 19, Ambo, EthiopiaTel +251 910 45 11 84Email benyamseifu77@gmail.comBackground: Globally, 95% of women wants to avoid pregnancy for at least two years after giving birth, but 70% of them are not using contraception; majority of them were from developing countries. Postpartum family planning (PPFP) enables families to avoid unplanned pregnancies following 12 months after childbirth. Different studies in Ethiopia showed that the majority of postpartum women do not use PPFP. Moreover, the level of PPFP knowledge and utilization in West Shewa, Oromia region of Ethiopia is unclear.Purpose: This study aimed to assess the knowledge, utilization and associated factors of postpartum family planning (PPFP) Oromia regional state, Ethiopia.Methods: A community-based cross-sectional study was conducted in Ambo town, West Shewa Zone of Oromia regional state from April 01 to July 30, 2019. A sample of 367 postnatal women participated in the study. An interview administered questionnaire was used to collect the data and the collected data were entered into Epi Info version 7.1 and analyzed with SPSS version 23. Study participants’ characteristics were described using frequency and percentage. Bivariate and multivariate logistic regression was carried out to identify the associated factors with the outcome variables.Results: A total of 354 women were participated in the study making a response rate of 96.4%. About 249 (70.3%) of the respondents had good knowledge about PPFP and 144 (40.7%) had utilized PPFP services. Higher education level [AOR= 3.4, 95% CI: 1.3– 6.9], history of family planning utilization [AOR= 2.8, 95% CI: 2.1– 4.4] and having ANC follow-up [AOR=2.1, 95% CI: 1.1– 4.0] had showed a positive association with knowledge of PPFP. Meanwhile, knowledge of PPFP [AOR=2.1, 95% CI: 1.6– 3.1], a grand multi-para women [AOR=1.7, 95% CI (1.3– 3.6)] and received routine PNC service [AOR=2.5, 95% CI: 1.3– 5.9] were associated with the utilization of PPFP.Conclusion and Recommendation: Although the majority of the women knew about PPFP, more than half of them did not utilize PPFP. Due emphasis should be given to improve the utilization of PPFP.Keywords: postpartum family planning, knowledge, utilization and associated factors